AI and Islamic Jurisprudence: Re-reading Contemporary Fatwās for Ethical Possibilities in Techno-Social Forms of Life - Muhammed Ameen Fazal (Universitas Islam Internasional Indonesia, 2026)
This study examines contemporary Islamic legal responses to Artificial Intelligence (AI) within the broader discourse on Islam’s engagement with modern science and technology. Historically, Muslim jurists (fuqahāʾ) and muftīs have responded to technological innovations through context-specific juristic reasoning rather than through simple acceptance or rejection. However, AI presents a qualitatively distinct challenge, raising questions about human reasoning, moral agency, religious authority, and knowledge production. Focusing on the 10th Annual Dār al-Iftāʾ al-Miṣrīyah Conference, “The Making of the Competent Muftī in the Age of Artificial Intelligence,” and the 26th session of the Majmaʿ al-Fiqh al-Islāmī al-Duwalī, this study analyzes how contemporary muftīs conceptualize the relationship between human expertise and machine-generated fatwās. Through textual analysis of conference papers, resolutions, and juristic discussions, it explores how Islamic legal thought defines the role of the muftī and distinguishes human juristic reasoning from AI-generated outputs. This study argues that AI differs from earlier technological innovations because it not only facilitates communication and calculation but also reshapes the conditions of knowledge production, social life, and ethical responsibility. This development exposes the limitations of positivist approaches that reduce fatwās to codified legal rulings or reactive, religious pronouncements. By recovering the fatwā as a historically situated mode of ethical and juristic reasoning, this study demonstrates that Islamic legal thought retains the capacity to generate new normative possibilities in the age of AI. While contemporary juristic discussions often remain constrained by positivist categories, the fatwā tradition offers conceptual resources for addressing the ethical challenges of increasingly AI-mediated forms of life and contributes to broader debates on Islamic law, technology, and the future of human moral agency.